(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the issue of control in the conditions of the higher education transition in the Republic of Kazakhstan to new educational standards on the example of the course «Russian language». Following aspects were considered the as the most important: the place of the course «Russian language» and its role in the vocational training system for a particular specialty, which competencies should be formed as a result of its study and how the organization of the educational process on the basis of competencies with its traditional orientation on KAS (knowledge, ability, skills). The article focuses on the independent work of students as a form of control and its final form – a student scientific-practical conference.